Debt Heyday and Economic Degrowth: The Collapse of Civilization - Cante, Freddy; Franco-Cuervo, Ana Beatriz (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose and hypothesis of this paper is to show that the rise of money (debts) is the spur of economic growth, but it is also the cause of underdevelopment and, furthermore, the collapse of global civilization. The methodology is based on a critical reading of the most relevant and heterodox economic literature, in order to clarify the concepts of monetary debt, real wealth, growth and also the collapse that past civilizations have experienced and which is now a global risk; this is complemented by some historical evidence, and by relevant statistical data, particularly on debt. The argument is not limited to a positive approach (how things are), but transcends towards a normative vision (how the world should be), for which ethical discussions are recurrently incorporated. Findings: first: money is imaginary wealth, which implies the creation of debts (which increase exponentially with the compound interest rate), which goes against real wealth, which is degraded and destroyed, due to entropic processes (accelerated by economic growth, in turn spurred by debts); second: underdevelopment is a creation (of dominant countries and institutions), to keep third world countries as importers of capital, and exporters of raw materials and mining-energy resources (to pay onerous public debts and imports); third: neoliberalism has been consolidated as a strong defense of the creators of various forms of money, which has been imposed from the Washington Consensus to that of Wall Street; and, fourth: due to the prolonged interaction between borrowers and lenders, a gigantic discount of the future has been produced, which translates into colossal destruction of future life (global warming and global collapse of civilization). Regarding the implications, for the purposes of heterodox economic policy, powerful arguments are offered to insist on non-payment of debts, because the bankruptcy and radical transformation of the financial system is a condition, sine qua non, to save life on the planet.